MODERN TREATMENT OF ASPHYXIA IN NEWBORNS - Tolipova Noila Kudratovna; Latipova Shakhnoza Akbarbekovna (Scholar Express Journals, 2023)
Among the many factors that damage the brain of newborns, hypoxia should be highlighted, which can be classified as a universal damaging agent. Asphyxia recorded in newborns is very often only a continuation of hypoxia, which began in utero. Intrauterine hypoxia and hypoxia in childbirth in 20-50% of cases is the cause of perinatal mortality, in 59% of cases it is the cause of stillbirth, and in 72.4% hypoxia and asphyxia become one of the main causes of fetal death in childbirth or early neonatal period
Keywords: Hypoxia; asphyxia; newborns; treatment